Genome-based analysis of infrequent Salmonella serotypes through the Thai pork production chain - Eiamsam-ang, Thanaporn; Tadee, Pakpoom; Pascoe, Ben; Patchanee, Prapas (Frontiers in Microbiology, 2022)
Salmonella is recognized as a prevalent zoonotic foodborne pathogen. Swine and pork are implicated as the important sources of Salmonellosis in humans. In Chiang Mai and Lamphun Provinces in northern Thailand, there has been a high prevalence of Salmonella persistence for over a decade. Infection is usually with the several dominant S. enterica serotypes, including serotypes Rissen and 1,4,[5],12:i:-. However, other serotypes also contribute to disease and are less well characterized. The whole genome sequencing data of 43 S. enterica serotypes isolated form pork production chain through 2011-2014, were used to evaluated on genetic diversity and ascertain the possibility source of Salmonella contamination based on Core Genome Multilocus Sequence Typing (cgMLST) approach. The Salmonella serotypes recovered from farm-slaughterhouses were descended from the same common ancestor and were re-circulating by swine environmental contamination. Conversely, the Salmonella contamination in the retail market represents cross-contamination from multiple sources, including decontaminated foodstuffs. Salmonella contamination in the pork production chain has the competency for host cell adhesion, host cell invasion, and intracellular survival, which is enough for the pathogenicity of salmonellosis. In addition, all of these isolates were multi-drug resistant Salmonella, which contained at least 10 antimicrobial resistance genes. This result indicated that these S. enterica serotypes also pose a significant public health risk. Our findings support the need for appropriate surveillance of food-animal products going to market to reduce public exposure to highly pathogenic, multi-drug resistant Salmonella. Acquiring information would motivate all stakeholders to reinforce sanitation standards throughout the pork production chain in order to eradicate Salmonella contamination and reduce the risk of salmonellosis in humans.